The role of moral values in the tourism service ,An analytical study - المشهداني, خليل ابراهيم; سالم, سالم حميد (Journal of Economics and Administrative Sciences, 2015)
Business Ethics play a major role in explaining the behavior of those interested in the management of tourism enterprises in the field of management gains, which sometimes turn to manipulation in the specification of the service of tourism and influence in the technical characteristics at the expense of the brand and market share, as well as misleading beneficiaries about the fact that the performance of the service of tourism, may depend activities tourist dramatically when submitting and sharing various services on the types of mutual relations the framework for moral distinct, in interaction or direct contact between producers of tourism services and tourists or their beneficiaries, in order to provide comfort and recreation and entertainment for the whole of tourists, which should be the subject of this activity is to study the phenomena the mutual relations between the variables of the process of tourism in community tourism through the correction on the moral values ​​of the tourism product as it can be a factor, either positive or negative in determining the characteristics of tourist services, either the research problem highlights the problem of differing estimate the role of the factors in the external environment in building moral values ​​among producers and tourists collectively or individually, and then flip it in the processes of interaction and exchange of social, economic, cultural and other, and highlights the importance of the study through addressed to the issue of moral values ​​and their role in shaping the human relationships between the tourism product and tourists, on the one hand and between the tourism product suppliers, processors and marketers on the other hand aims study to identify the degree of the role of external factors in moral values ​​and the reflection of the commitment by the tourism product in the production processes of tourist services and to identify the role of external factors of influence in the moral values ​​of the tourism product in the production processes of service and tourist analyzed logically, and to know the impact on the tourism product and influence in moral values​​, researchers have come to the results of statistical analysis through the interrelationships between the variables of the study by researchers at the tables, including the vehicle reached by researchers through pairing and compatibility tests to test hypotheses for research